Behavioral Responses of Drosophila suzukii (Diptera: Drosophilidae) to Blends of Synthetic Fruit Volatiles Combined With Isoamyl Acetate and β-Cyclocitral - Bolton, L. Grant; Piñero, Jaime C.; Barrett, Bruce A. (Frontiers in Ecology and Evolution, 2022)
Baits and lures for trapping and monitoring the invasive vinegar fly Drosophila suzukii Matsumura (Diptera: Drosophilidae) are currently derived from fermentation volatiles. Volatile organic compounds from alternative sources could improve monitoring efforts and optimize capture of gravid females. Through electroantennography and behavioral assays, we evaluated fly responses to blends of selected synthetic fruit volatiles in combination with the fruit compound isoamyl acetate and the strawberry leaf terpenoid β-cyclocitral. Blends that were attractive to both male and female D. suzukii were then evaluated for attractiveness to a non-target drosophilid, D. melanogaster. A simple 3-component blend of isoamyl acetate, β-cyclocitral and methyl butyrate was attractive to D. suzukii, particularly females, relative to fresh blueberry volatiles. The 3-component blend was not attractive to D. melanogaster. Additional research is needed to determine the effectiveness of this blend to attract D. suzukii under field conditions.